Competition in the Portuguese economy: estimated price-cost margins under imperfect labour markets - Jo\~ao Amador; Ana Cristina Soares (European Central Bank (ECB), 2014)
This article estimates price-cost margins for the Portuguese markets in a context of imperfect competition in the labour market. The database used includes virtually the universe of Portuguese firms for the period 2005-2009. The results strongly reject the hypothesis of perfect competition in both labour and product markets. Estimated price-cost margins are very heterogeneous across markets and the average for the overall economy ranges between 25 and 28 per cent, depending on the variables used to weight each market. In addition, the tradable sector presents a lower price-cost margin than the non-tradable sector. According to the methodology used, workers' bargaining power in the Portuguese economy is approximately 13 per cent, without a clear distinction between tradable and non-tradable sectors. Finally, workers' bargaining power is highly and positively correlated with price-cost margins across markets.
Keywords: L10; L60; O50; 330; market competition; Portuguese economy; production function